The Role of the Body Clock in Asthma and COPD: Implication for Treatment - Karolina Krakowiak; Hannah J. Durrington (Pulmonary Therapy, 2018)
Abstract Asthma exhibits a marked time of day variation in symptoms, airway physiology, and airway inflammation. This is also seen in chronic obstructive pulmonary disease (COPD), but to a lesser extent. Our understanding of how physiological daily rhythms are regulated by the circadian clock is increasing, and there is growing evidence that the molecular clock is important in the pathogenesis of these two airway diseases. If time of day is important, then it follows that treatment of asthma and COPD should also be tailored to the most efficacious time of the day, a concept known as ‘chronotherapy’. There have been a number of studies to determine the optimal time of day at which to take medications for asthma and COPD. Some of these agents are already used ‘chronotherapeutically’ in practice (often at night-time). However, several studies investigating systemic and inhaled corticosteroids have consistently shown that the best time of day to take these medications for treating asthma is in the afternoon or early evening and not in the morning, when these medications are often prescribed. Future, large, randomized, placebo-controlled studies of systemic and inhaled corticosteroids in asthma and COPD are needed to inform clinical practice. Digital Features This article is published with a graphical abstract to facilitate understanding of the article. To view digital features for this article go to the Supplementary Information of the article.